Human herpesvirus 6 meningitis in an adult. Issue 2 (2nd April 2020) - Maniam, Ganesh B.; Wilkerson, Hannah; Milton, John Scott
Abstract: Many cases of viral meningitis are idiopathic, but increased utilization of polymerase chain reaction testing has enabled physicians to better recognize rare causes of viral meningitis. This will likely continue to improve the rate of causative agent identification in seemingly idiopathic viral meningitis, including this case of human herpesvirus 6 (HHV-6) meningitis in an immunocompetent adult patient. More common viral etiologies need to be excluded before diagnosing HHV-6 meningitis, as this maximizes pretest probability and therefore increases validity of a positive result. By efficiently diagnosing HHV-6 meningitis, proper treatment protocols can be initiated earlier to reduce morbidity and mortality. Given the rarity of HHV-6 meningitis in immunocompetent adults, there are no established standard treatment guidelines; previous reported cases, as well as this case, suggest that either intravenous ganciclovir or intravenous foscarnet are the most reasonable first-line treatment options.